Research progress on the proteins involved in African swine fever virus infection and replication - Duan, Xianghan; Ru, Yi; Yang, Wenping; Ren, Jingjing; Hao, Rongzeng; Qin, Xiaodong; Li, Dan; Zheng, Haixue (Frontiers in Immunology, 2022)
African swine fever (ASF) is an acute, hemorrhagic and highly contagious infectious disease caused by African swine fever virus (ASFV), which infects domestic pigs or wild boars. It is characterized by short course of disease, high fever and hemorrhagic lesions, with mortality of up to 100% from acute infection. Up to now, the lack of commercial vaccines and effective drugs has seriously threatened the healthy economic development of the global pig industry. ASFV is a double-stranded DNA virus and genome varies between about 170-194 kb, which encodes 150-200 viral proteins, including 68 structural proteins and more than 100 non-structural proteins. In recent years, although the research on structure and function of ASFV-encoded proteins has been deepened, the structure and infection process of ASFV are still not clear. This review summarizes the main process of ASFV infection, replication and functions of related viral proteins to provide scientific basis and theoretical basis for ASFV research and vaccine development.